2010
DOI: 10.1515/ijdhd.2010.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parent and child pain and functioning in a pediatric chronic pain sample: a mixed methods approach

Abstract: This study employed a mixed-method design to test sex-specific parent-child pain associations. Subjects were 179 chronic pain patients aged 11–19 years (mean = 14.34; 72% female) presenting for treatment at a multidisciplinary, tertiary clinic. Mothers and children completed questionnaires prior to their clinic visit, including measures of children’s pain, functioning and psychological characteristics. Mothers also reported on their own pain and psychological functioning. Interviews were conducted with a sub-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…CPM is thought to reflect central pain inhibitory processes and is relatively unstudied in children. We have also demonstrated relationships between maternal psychological factors and daughters’ pain and anxiety responses to traditional, static laboratory pain tasks 18,29,30. Both the current study and this prior research suggest alignment between mother and daughter pain-related psychological functioning.…”
Section: Discussionsupporting
confidence: 74%
“…CPM is thought to reflect central pain inhibitory processes and is relatively unstudied in children. We have also demonstrated relationships between maternal psychological factors and daughters’ pain and anxiety responses to traditional, static laboratory pain tasks 18,29,30. Both the current study and this prior research suggest alignment between mother and daughter pain-related psychological functioning.…”
Section: Discussionsupporting
confidence: 74%
“…Investigations on the relationship between parental pain and adolescent pain have shown conflicting results. While some studies [22][23][24]48,49 found an association, other studies [19][20][21]50,51 did not. Several interpretations may explain this discrepancy.…”
Section: Commentmentioning
confidence: 93%
“…Reporting has also varied; some studies 45,53 have used parental report of children's pain, one study 51 used children's report about their parents' pain, and other studies 19,20 have used pain reports both from the children and from the parents. However, other studies 22,23,49 have reported from only one parent, usually the mother. When examining the relationship between parental pain and adolescent pain, it is essential to have self-reports from all involved.…”
Section: Commentmentioning
confidence: 99%
“…38,39,125 Parent—child communication and interaction styles investigated in the context of pediatric chronic pain have found associations between high conflict and low adolescent autonomy with increased depressive symptoms 86 and lower autonomy than expected for age in youth with pain. 42 …”
Section: Potential Mechanisms For the Transmission Of Riskmentioning
confidence: 99%